Given the system of equations, what is the solution?
5x - 4y = 7
x = 5 - y

Question

Asked 3/28/2014 12:52:30 PM

Updated 9/15/2014 7:46:29 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [9/15/2014 7:36:49 AM], Edited by andrewpallarca [9/15/2014 7:46:29 AM]

japs2310qa|Points 1979|

Question

Asked 3/28/2014 12:52:30 PM

Updated 9/15/2014 7:46:29 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [9/15/2014 7:36:49 AM], Edited by andrewpallarca [9/15/2014 7:46:29 AM]

Rating

3

The solution for 5x - 4y = 7, x = 5 - y is x = 3, y =2 ,which is not in the options .

Put x = 5 - y in 1th equation

5x -4y = 7

5( 5 - y) - 4y = 7

25 - 9y = 7

-9y = -18

y = 2

x = 5 - y

x = 5-2

x = 3

Put x = 5 - y in 1th equation

5x -4y = 7

5( 5 - y) - 4y = 7

25 - 9y = 7

-9y = -18

y = 2

x = 5 - y

x = 5-2

x = 3

Added 9/15/2014 7:40:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/15/2014 7:46:21 AM], Rated good by andrewpallarca

Solve 4(x - 3) - 2(x - 1) > 0.
{x | x -5}
{x | x > 5}
{x | x < 5}

Question

Expert Answered

Updated 3/28/2014 1:06:21 PM

1 Answer/Comment

4(x - 3) - 2(x - 1) > 0

(4x - 12) - (2x + 2) > 0

2x - 10 > 0

2x > 0 + 10

2x > 10

x > 10/2

x > 5

(4x - 12) - (2x + 2) > 0

2x - 10 > 0

2x > 0 + 10

2x > 10

x > 10/2

x > 5

Added 3/28/2014 1:06:19 PM

This answer has been confirmed as correct and helpful.

The system shown has _____ solution(s).
y = x + 1
2y - x = 6
no
one
infinite
**Weegy:** y=x+12_y-x=2...
Replace all occurrences of y with the solution found by solving the last equation for y. [ In this case, the value substituted is x+12.
y=x+12_(x+12)-x=2..
Remove the parentheses around the expression x+12.
y=x+12_x+12-x=2...
Since x and -x are like terms, add -x to x to get 0.
y=x+12_0+12=2...
Remove the 0 from the polynomial; adding or subtracting 0 does not change the value of the expression.
y=x+12_12=2...
Since 12 is not equal to 2, there are no solutions.
The system shown has no Solutions. ] (More)

Question

Expert Answered

Updated 3/30/2014 9:46:19 PM

1 Answer/Comment

y = x + 1, the first equation

2y - x = 6, the second equation

Replace y in the second equation with the first one we get:

2(x + 1) - x = 6

solve the equation we get x = 4

so, y = 4 + 1 = 5

The system y = x +1, 2y - x = 6 has one solution (4, 5)

2y - x = 6, the second equation

Replace y in the second equation with the first one we get:

2(x + 1) - x = 6

solve the equation we get x = 4

so, y = 4 + 1 = 5

The system y = x +1, 2y - x = 6 has one solution (4, 5)

Added 3/30/2014 9:46:09 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/30/2014 9:52:50 PM]

27,930,158

questions answered

There are no comments.